THE INFLUENCE OF FEEDBACK GIVEN BY LECTURERS ON GRAMMATICAL ERRORS IN 2nd SEMESTER STUDENTS' WRITING IN ENGLISH DEPARTMENT MUHAMMADIYAH UNIVERSITY OF SURAKARTA IN 2015/2016 ACADEMIC YEAR - SARAFINA, ANNISA, Drs. Djoko Srijono, M.Hum (2016)
This research is about the influence of feedback given by the lecturer in writing. The purpose of the research is to describe the impact of feedback given by lecturer toward to students' writing competence and describe whether giving feedback from lecturer is effective to improve the students' writing competence. This research focuses on investigating the students' perceptions feedback given by lecturer and the impact of the feedback and notes given by the lecturer. The data were collected through observations, interviews, and documentation. The result of the research shows that the average of students' error before and after they get feedback is decreased. It could be concluded that the feedback from lecturer in the writing process could improve the students' writing competence. Besides, feedback from lecturer makes them learn from their error that they do in their writing. From their correction from the lecturer, they can learn from it. They can revise their writing and make less error after get feedback from lecturer.